Peran PT. Bank SUMUT Syariah KCP Binjai dalam Mengembangkan Usaha Mikro Kecil dan Menengah Melalui Penyaluran Pembiayaan Murabahah - Eka May Selly; Ahmad Fuadi (Al-Istimrar: Jurnal Ekonomi Syariah, 2022)
Micro, Small and Medium Enterprises (MSMEs) are the largest group of economic actors in the Indonesian economy and are the largest sector contributing to national development. Micro, Small and Medium Enterprises (MSMEs) also create sizable job opportunities for domestic workers, so that they are very helpful in efforts to reduce unemployment. Seeing the existence of the micro business sector which is managed by business actors who have problems with limited capital. With the existence of Islamic Banking, it can assist in providing additional capital through financing products that can be used by business actors to support and develop their business for Micro, Small and Medium Enterprises (MSMEs). In practice, Islamic Financial Institutions mostly use murabaha products in the distribution of MSME financing. In Indonesia, the dominance of murabahah financing in Islamic banks compared to financing with other contracts reached 57%, even though most users of other types of contracts switched to murabahah. One of the branches that focus on developing Micro, Small and Medium Enterprises (MSMEs) is in Binjai City, one of which is by channeling murabahah financing to Micro, Small and Medium Enterprises. The type of research conducted is descriptive qualitative research. The research approach taken in this study is an empirical approach. The role played by PT. Bank SUMUT Syariah KCP Binjai in Developing Micro, Small and Medium Enterprises (MSMEs), in Developing Micro, Small and Medium Enterprises, namely in the following ways: Providing Capital Efforts for MSMEs, Easing and Facilitating MSMEs in Obtaining Financing, Providing Assistance to MSME Actors who Receive Financing, Holding Entrepreneurship Seminars and Workshops. With the existence of the Indonesian Sharia Bank, it is possible to increase the productivity of micro, small and medium enterprises in the city of Bengkulu. With the presence of the Bank Indonesian Sharia is expected to change the mindset of MSME actors to switch from loan sharks and conventional banks that use the usury system to Islamic Bank financing based on sharia principles.